2019
DOI: 10.4314/wiojms.v18i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea and lipid removal from Carcharhinus leucas and Galeocerdo cuvier white muscle on carbon and nitrogen stable isotope ratios

Abstract: Aims and scope: The Western Indian Ocean Journal of Marine Science provides an avenue for the wide dissemination of high quality research generated in the Western Indian Ocean (WIO) region, in particular on the sustainable use of coastal and marine resources. This is central to the goal of supporting and promoting sustainable coastal development in the region, as well as contributing to the global base of marine science. The journal publishes original research articles dealing with all aspects of marine scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…However, LE had a similar effect on δ 15 N values as DW, suggesting that LE is removing the same amount of urea as DW. This conflicts with previous studies that found no effect of LE on δ 15 N (Burgess and Bennett, 2017;Carlisle et al, 2017) or a small positive shift (Hussey et al, 2010b;Martin and Jaquemet, 2019) but agrees with large increases in δ 15 N found by Logan and Lutcavage (2010) and Marcus et al (2017). As LE and DW have the same effect on δ 15 N, but LE and DW+LE cause a more positive δ 13 C value relative to DW, this suggests that some lipid removal is taking place.…”
Section: Musclecontrasting
confidence: 94%
See 1 more Smart Citation
“…However, LE had a similar effect on δ 15 N values as DW, suggesting that LE is removing the same amount of urea as DW. This conflicts with previous studies that found no effect of LE on δ 15 N (Burgess and Bennett, 2017;Carlisle et al, 2017) or a small positive shift (Hussey et al, 2010b;Martin and Jaquemet, 2019) but agrees with large increases in δ 15 N found by Logan and Lutcavage (2010) and Marcus et al (2017). As LE and DW have the same effect on δ 15 N, but LE and DW+LE cause a more positive δ 13 C value relative to DW, this suggests that some lipid removal is taking place.…”
Section: Musclecontrasting
confidence: 94%
“…However, in contrast, δ 13 C values of muscle treated with both LE and DW+LE were similar to the control δ 13 C value, suggesting that 13 C-depleted compounds such as lipids are being removed and potentially countering the decrease in δ 13 C values caused by the removal of urea. All treatments in all species resulted in a large increase in muscle δ 15 N values (0.9-1.3 ) displaying the same range of values as a variety of other elasmobranch species (Burgess and Bennett, 2017;Marcus et al, 2017;Martin and Jaquemet, 2019) confirming previous findings that muscle needs to be treated for urea regardless of species and size (Kim and Koch, 2012;Li et al, 2016;Carlisle et al, 2017). However, LE had a similar effect on δ 15 N values as DW, suggesting that LE is removing the same amount of urea as DW.…”
Section: Musclesupporting
confidence: 81%
“…Although shark muscle generally contains low lipid content (<1%) (Meyer et al, 2017), lipids are depleted in 13 C and shark osmoregulatory strategy induce a significant urea retention which is depleted in 15 N. This may cause bias in the interpretation of the δ 13 C and δ 15 N, and therefore requires a mathematical normalization for the δ 13 C and δ N values following urea and lipid extraction in several species of sharks (Y. . Here, we applied the normalization equations established for the bull and the tiger shark from La Réunion Island, for each species and each sex (Martin and Jaquemet, 2019).…”
Section: Muscle δ 13 C and δ 15 N Valuesmentioning
confidence: 99%
“…Ammonia in the muscle tissues of elasmobranchs can have effects on SI values, and studies have suggested that rinsing samples in deionized water can remove the urea (Li et al, 2016). When comparing shark muscle samples with lipids extracted versus samples that were both lipid-extracted and deionized-water-rinsed, the urea extracted samples had d 15 N values increased by just under 1.0‰ and d 13 C values decreased by just under 1.0‰ (Martin and Jaquemet, 2019). To our knowledge, this method has not been tested in ammoniacal squid tissues and is not currently standard among SIA of squid muscle.…”
Section: Limitationsmentioning
confidence: 99%